Executive Strategic Planning as a Pillar of Building School Competitive Advantage in a Dynamic Era - Kiki Aryani; Agus Rahayu; Lili Adi Wibowo; Puspo Dewi Dirgantari; Neni Nuraeni (UIN Sunan Gunung Djati Bandung, 2025)
Rapid changes in the educational environment require schools to have adaptive and visionary leadership strategies. Competition between educational institutions and increasing public expectations for service quality add to the complexity of the challenges of managing educational institutions. In this context, the strategic role of school executives becomes crucial as the determinant of direction and the main driver of institutional transformation. This study aims to analyze how school executives design and implement strategies in building competitive advantages amidst the ever-evolving dynamics. This study uses a qualitative approach by relying on data from various relevant sources, such as previous research and institutional strategic documents. The data obtained are analyzed interpretively to reveal patterns and tendencies in strategic leadership practices in schools. The results of the study indicate that school executives have a central role in determining the direction of policies and program priorities that impact the quality and competitiveness of institutions. Success in building competitiveness is greatly influenced by the leadership's ability to respond to change, manage resources, and involve stakeholders. Although there are various challenges in implementing strategies, consistent and reflective leadership can maintain the continuity of planning and implementation on an ongoing basis.